Investigating Commute Mode and Route Choice Variabilities in Jakarta Using Multi-Day GPS Data - Zainal N. Arifin; Kay W. Axhausen (International Journal of Technology, 2014)
This paper reports on findings regarding the day-to-day dynamic behavior of commuters’ mode and route choices in Jakarta. Ninety-three commuters using Global Positioning System (GPS) devices during a one-week period were observed. The observation proves the presence of dynamic behavior in choosing both modes and routes for commuting in Jakarta. Car drivers and motorcyclists frequently change their routes, especially during work-to-home trips. Motorcyclists were more dynamic in choosing their routes than were car drivers. This case study revealed a unique pattern of mode and route choice behavior, which can be used for developing a mode and route choice model for Jakarta.